Evaluation of Green Port Factors and Performance: A Fuzzy AHP Analysis. (23rd December 2013) - Chiu, Rong-Her; Lin, Le-Hui; Ting, Shih-Chan
Abstract : Due to the occurrence of abnormal global environmental change, the concept of sustainable development becomes more and more important. Port plays an important role in economic development for a country. To tackle the environmental pollution coming from the construction and operation of a port, the green concept emerged as a solution. Founded on the previous literatures, the current study formulates a Fuzzy AHP model including five dimensions and thirteen factors as the guidelines for green port operation. The results of empirical study point out the top five priority attributes of green port operation which are: hazardous waste handling, air pollution, water pollution, port greenery, and habitat quality maintenance. The FAHP model is a good referral for decision makers of port organizations to forge a "greener" port operation; it also can be used to evaluate the port's green operation performance.